Predictors of prostate volume reduction following neoadjuvant cytoreductive androgen suppression - Jethwa, Krishan R.; Furutani, Keith M.; Mynderse, Lance A.; Wilson, Torrence M.; Choo, Richard; King, Bernard F.; Bergstralh, Eric; Davis, Brian J. (Journal of Contemporary Brachytherapy, 2016)
Purpose: Limited duration cytoreductive neoadjuvant hormonal therapy (NHT) is used prior to definitive radiotherapeutic management of prostate cancer to decrease prostate volume. The purpose of this study is to examine the effect of NHT on prostate volume before permanent prostate brachytherapy (PPB), and determine associated predictive factors. Material and methods : Between June 1998 and April 2012, a total of 1,110 patients underwent PPB and 207 patients underwent NHT. Of these, 189 (91.3%) underwent detailed planimetric transrectal ultrasound before and after NHT prior to PPB. Regression analysis was used to assess predictors of absolute and percentage change in prostate volume after NHT. Results: The median duration of NHT was 4.9 months with inter quartile range (IQR), 4.2-6.6 months. Prostate-specific antigen (PSA) reduced by a median of 97% following NHT. The mean prostate volume before NHT was 62.5 ± 22.1 cm 3 (IQR: 46-76 cm 3 ), and after NHT, it was 37.0 ± 14.5 cm 3 (IQR: 29-47 cm 3 ). The mean prostate volume reduction was 23.4 cm 3 (35.9%). Absolute prostate volume reduction was positively correlated with initial volume and inversely correlated with T-stage, Gleason score, and NCCN risk group. In multivariate regression analyses, initial prostate volume (p < 0.001) remained as a significant predictor of absolute and percent prostate volume reduction. Total androgen suppression was associated with greater percent prostate volume reduction than luteinizing hormone releasing hormone agonist (LHRHa) alone (p = 0.001). Conclusions : Prostate volume decreased by approximately one third after 4.9 months of NHT, with total androgen suppression found to be more efficacious in maximizing cytoreduction than LHRHa alone. Initial prostate volume is the greatest predictor for prostate volume reduction.